Primary familial brain calcification presenting with parkinsonism and motor complications caused by a novel SLC20A2 variant: a case report - Sun, Dandan; Wang, Yu; Wang, Jiawei; Wang, Shijing; Zhu, Ling; Xia, Kun; Zhang, Yunyun; Wang, Xun (Frontiers in Neurology, 2024)
Primary familial brain calcification (PFBC), also known as Fahr’s disease, is a central nervous system calcium deposition disorder with symmetrical basal ganglia calcification. Most PFBC cases are caused by SLC20A2 gene variant. We report a Chinese female patient with PFBC and dopamine-responsive parkinsonism who had motor fluctuations and dyskinesia and recovered effectively after symptomatic medication adjustment. A novel heterozygous missense variant was found by whole-exome sequencing and proven harmful by family validation and genetic analysis. This example expands the phenotype of SLC20A2-associated PFBC patients and shows the clinical efficacy of dopaminergic replacement treatment.